INDONESIA DIPLOMACY THROUGH THE SHERPA TRACK IN THE G20 FORUM 2015-2022 - Farhan Firdaus; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The G20 is a non-formal international forum that was established against the backdrop of concerns about global economic issues. Over time, the G20 has evolved into a complex international forum with two main tracks: the finance track, which focuses on economic, financial, and fiscal issues, and the sherpa track, which addresses non-systemic issues that can impact the economy or human security, such as development, humanitarian issues, social poverty, technology, health, and others. The sherpa track consists of two main discussions: the working group (government) and the engagement group (non-governmental). Indonesia has been a member of the G20 since its formation, along with 18 other countries and one regional organization. Indonesia is part of the G20 due to its large Gross Domestic Product (GDP). In 2022, Indonesia held the G20 presidency and brought forward several national issues and interests. Indonesia demonstrated its diplomatic efforts, such as its active participation in the sherpa track. This research employs a qualitative method, involving data collection through interviews and document analysis, drawing from books, journal articles, news, reports, and websites related to Indonesia's diplomacy in the G20 forum through the sherpa track. The results of this study show that Indonesia's diplomacy in the sherpa track demonstrates good engagement. However, Indonesia's status as a middle power poses challenges in its efforts to voice, represent, and advocate for its interests in the forum alongside great powers. To make Indonesia's diplomacy effective, it is necessary to build strength and capacity in collaboration with other middle-power countries. Keywords : G20, sherpa track, diplomacy, Indonesia, middle power